THE DECREASE OF AIRLINE OCCUPATIONAL ENVIRONMENTAL RISK FACTORS. LEGISLATIVE AND MEDICAL ASPECTS - V. E. Andrusov; Y. G. Khudyakov (Научный вестник МГТУ ГА, 2017)
Russian Federation is entering a new system of Occupational standards as norm of competence that people are expected to achieve in their work, and the knowledge and skills they need to apply effectively. There may be conflicts in professional co-operation between the new system of Occupational standards and the old system of Managers, specialists and workforce qualification reference books. It may affect the common area of occupational environmental hazards. Employees, who passed compulsory medical examination, can have poor health conditions. It affects the inability of the employees to perform their aircraft maintenance duties. It may be a particular occupational environment factor. A five-point scale of possible damage severity was proposed for this factor. It is known that a sick employee's duties are redistributed among the remaining employees. Redistributing of a sick employee's duties increases the task load of the remaining ones in terms of overtime work for instance. It, ultimately, may compromise normal operation of employees. The results can be used when taking management decisions in process organization of airlines, as well as in other industries.